Integration of science, environmental (green) and literary education through the use of children’s and young people’s literature (juvenile fiction, young adults’ literature) in the practice of primary school teachers - Szabó, Ildikó; Bódis-Nagy, Franciska (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2024)
According to the current regulation of the National Core Curriculum in Hungary, science education should be embedded in the field of Hungarian language and literature through the processing of informative texts aimed at text comprehension and knowledge extension in the first two grades of primary education. The teaching of environmental studies starts in the third grade and builds on the developments and activities in the fields of technology and design, Hungarian language and literature, visual culture, mathematics and ethics in the framework of the subjects of technology and design, Hungarian language and literature, visual culture and ethics in the first and second grades. The first cycle of primary education for grades 1–4, which followed the provisions of National Core Curriculum, has been completed in the school year 2023/2024, so it is examining how the aforementioned public education regulation has affected the everyday school practice in grades 1–4, especially seeing into how and in what ways the content of literature teaching has changed with the introduction of science studies content; whether practisioners have the opportunity to introduce pupils to fiction related to nature, environmental studies, environmental protection and the created world through optional reading materials, and to what extent teachers are familiar with contemporary, age-appropriate literature on such topics. The present paper presents the results of an empirical, small-sample (74 respondents) questionnaire survey on whether practising teachers in grades 1–4, when using optional reading materials in classrooms, pay attention to linking literary education with science education.